Analisis Pengaruh Implementasi Sistem Informasi Manajemen Keuangan Daerah (SIMDA), Kualitas Sumber Daya Manusia Dan Dukungan Manajemen Puncak Terhadap Kualitas Laporan Keuangan Daerah Provinsi Papua - Haluk, Desy I.; Allo Layuk, Paulus K.; Kambuaya, Quincy F. (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2024)
The aim of this research is to analyze the influence of the implementation of the Regional Financial Management Information System (SIMDA), the quality of human resources and top management support on the quality of regional financial reports in Papua Province. The sampling technique for respondents was carried out using purposive sampling. Purposive sampling technique is a technique for sampling data sources with certain considerations. The samples used in this research were auditors at the inspectorate, BPKAD employees consisting of accounting, bookkeeping sub-sector, asset sector, goods SIMDA, asset reporting and depreciation. Meanwhile, the OPD consists of the OPD head, treasurer and Regional Apparatus Organization Financial Administration Officer (PPK-OPD). The number of OPDs in Papua Province is 35 OPDs consisting of 5 Bureaus, 8 Services, 15 Agencies, 3 Hospitals, 1 Inspectorate, 2 Secretariats and Civil Service Police and Regional Disaster Management Units. The sample in this research was 185. The method used in this research was multiple regression analysis to test the relationship between several independent variables and one dependent variable. The results of the analysis show that the implementation of SIMDA has a significant effect on the quality of the financial reports of Regional Apparatus Organizations (OPD) in Papua Province. The quality of human resources has a significant effect on the quality of the financial reports of Regional Apparatus Organizations (OPD) in Papua Province. Top management support has a significant effect on the quality of the financial reports of Regional Apparatus Organizations (OPD) in Papua Province. The implementation of SIMDA, the quality of human resources and top management support simultaneously influence the quality of the financial reports of Regional Apparatus Organizations (OPD) in Papua Province.